Dendropanax morbifera Leaf Extracts Improved Alcohol Liver Injury in Association with Changes in the Gut Microbiota of Rats - Taekil Eom; Gwangpyo Ko; Kyeoung Cheol Kim; Ju-Sung Kim; Tatsuya Unno (MDPI AG, 2020)
This study evaluated the protective effects of Dendropanax morbifera leaf (DML) extracts in the liver due to excessive ethanol consumption. Our results showed that the ethanol extract had better antioxidant activity than the water extract, likely due to the higher levels of total flavonoid and phenolic compounds in the former. We found that the main phenolic acid was chlorogenic acid and the major flavonoid was rutin. Results from the animal model experiment showed concentration-dependent liver protection with the distilled water extract showing better liver protection than the ethanol extract. Gut microbiota dysbiosis induced by alcohol consumption was significantly shifted by DML extracts through increasing mainly Bacteroides and Allobaculum. Moreover, predicted metabolic activities of biosynthesis of beneficial monounsaturated fatty acids such as oleate and palmitoleate were enhanced. Our results suggest that these hepatoprotective effects are likely due to the increased activities of antioxidant enzymes and partially promoted by intestinal microbiota shifts.